DIVERSITAS SERANGGA ORDO ORTHOPTERA PADA LAHAN GAMBUT DI KECAMATAN LALAN KABUPATEN MUSI BANYUASIN - Irham Falahudin; delima engga mareta; Indah Ayu puji rahayu (Bioilmi: Jurnal Pendidikan, 2015)
Peatlands are one of the ecosystems that have a very high biodiversity of flora and fauna both. One animal that has an abundant amount in peatlands are insects. This is a descriptive qualitative study conducted in october carried on peatland in District Lalan Banyuasin district. Catching insects is done by using sthe sweep net, pitfaal traps and light traps in the risearch results in the identification of UIN Raden Fatah Biology Laboratory Palembang insect species diversity index (H) were analyzed using the Shannon-Weiner calculations. The results of this study indicate that insects are caught in Peatland consists of 93 individual 6 Family and 12 species. Insects that dominates in Peatlands District of Lalan Musi Banyuasin is Atractomorpha crenulata , Oxyachinensis and Valanga nigricornis , and insects that have the fewest number is Stagmomantis carolina , blatta orientali ( L ) and Periplenata americana ( L ). The Shannon diversity index values insect - Weiner ( H ) shows the value of 1.62 which means that the diversity of insect species that exist in Peatlands ( medium ).